RESISTENSI IDENTITAS MASYARAKAT DESA ADAT BUALU DALAM FORUM NUSA DUA BERSATU DI TENGAH ARUS GLOBALISASI PARIWISATA - Ida Bagus Putu Surya Suputra (STIE BIITM, 2020)
ABSTRACTThis article aims to elevate the Bualu Indigenous Village community that has beenmarginalized in the midst of globalization. With the current of globalization and thedevelopment of tourism driven by the capitalists led to the marginalization of the BualuIndigenous Village community and the loss of their local identities. Identity becomes a role toshow identity. And identity becomes a highly visible one based on character in each region,so that it has a difference between one regional identity with another, as well as from oneethnic group to another. So with the growth of a true awareness of the pressures in the midstof modernization, there arises an ideological resistance by building a unity called the NusaDua Bersatu Forum. This forum is a unifying forum for the people of Adat Bualu Village inparticular and the Benoa village in general and does not rule out the possibility of alsoestablishing close relations with other villages. So the writer found several problems, namelywhat caused the marginalized community of Bualu Indigenous Village? and how theresistance form of the Bualu Indigenous Village community through the Nusa Dua UnitedForum. This writing uses qualitative methods.